5‐aminolaevulinic acid patch‐photodynamic therapy in the treatment of actinic cheilitis. Issue 6 (29th August 2017) - Radakovic, Sonja; Tanew, Adrian
Summary: Background: Actinic cheilitis (AC) is a common disease caused by chronic ultraviolet exposure. Objective: Alacare is a self‐adhesive, skin coloured 5‐aminolaevulinic acid (ALA) patch that has been developed for the treatment of mild to moderate actinic keratosis (AK). Considering the good results in the treatment of AK, the standardized delivery of ALA and the simple application Alacare patch‐ photodynamic therapy (PDT) appears as an interesting treatment option for AC. Methods: We retrospectively assessed the efficacy, tolerability and cosmetic outcome of Alacare patch‐PDT in eleven patients with AC. After occlusion with the Alacare patches for 4 hours, the AC lesions were illuminated with narrowband red light and a dose of 37 J/cm 2 . All patients were clinically assessed for efficacy, side effects and cosmetic outcome at 3, 6, 9 and 12 months after treatment. Results: Complete clinical response at the 3‐month follow‐up was achieved in eight of 11 patients (72, 7%) and 12 of 15 AC lesions (80, 0%), respectively. Up to the final 12‐month follow‐up, a recurrence was observed in two lesions. The complete clinical cure rate at 1 year after Alacare patch‐PDT, thus, was 66, 6% (10/15 lesions). The cosmetic outcome of the treatment was excellent in all cases. Conclusion: Alacare patch‐PDT was found to have substantial efficacy in the treatment of mild to moderate AC. Given its ease of use, absence of long‐term side effects and the excellent cosmetic results Alacare patch‐PDT might be considered as a promising new treatment option for the management of AC.